2013
DOI: 10.1111/liv.12092
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of liver fibrosis by computerized morphometry in naïve patients with chronic hepatitis B and C

Abstract: As compared to CHB, amount of fibrosis is greater in CHC for F ≤ 2 patients, mainly because of higher perisinusoidal fibrosis. These data illustrate difficulty to assess early fibrosis stages by non-invasive methods, and support the need for specific cut-offs in CHB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 48 publications
3
25
1
Order By: Relevance
“…A few morphometric studies have focused on the different fibrosis compartments in CHC, [24][25][26][27][28] but owing to variations in methods, patient populations, and study goals, the results are hardly comparable to ours and between each other. The largest series in nontreated patients with chronic viral hepatitis showed that perisinusoidal fibrosis was twice more prominent in chronic hepatitis C than in chronic hepatitis B in early fibrosis stages (Fr2).…”
Section: Discussioncontrasting
confidence: 39%
See 3 more Smart Citations
“…A few morphometric studies have focused on the different fibrosis compartments in CHC, [24][25][26][27][28] but owing to variations in methods, patient populations, and study goals, the results are hardly comparable to ours and between each other. The largest series in nontreated patients with chronic viral hepatitis showed that perisinusoidal fibrosis was twice more prominent in chronic hepatitis C than in chronic hepatitis B in early fibrosis stages (Fr2).…”
Section: Discussioncontrasting
confidence: 39%
“…The largest series in nontreated patients with chronic viral hepatitis showed that perisinusoidal fibrosis was twice more prominent in chronic hepatitis C than in chronic hepatitis B in early fibrosis stages (Fr2). 28 This is an interesting finding as, unlike fibrosis in alcoholic or nonalcoholic steatohepatitis, perisinusoidal fibrosis has not been classically described as a significant lesion in CHC and is not included in the most used histological scores. In addition, a good correlation was observed between perisinusoidal fibrosis and stellate cell activation highlighted by a-smooth muscle actin immunostaining.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…had control of the data. Between March 2012 and October 2013, 173 consecutive Asian patients with chronic HBV infection referred to the division of infectious diseases of our Asian hospital for medical treatment were initially included in the study if (a) they were 18 years old or older without known or recent pregnancy, (b) they planned to undergo a biopsy during their hospitalization or underwent histologic examination within 3 months of hospitalization, (c) they had HBV surface antigen for more than 6 months and serum HBV DNA levels higher than 10 5 copies per milliliter or persistent or intermittent increase in other studies have demonstrated histologic differences between chronic HCV and chronic HBV fibrotic patterns, noting higher perisinusoidal fibrosis in chronic HCV infection for patients with a fibrosis stage ("F" stage) of F2 (8). Hence, when comparing hepatic tissue with the same severity of fibrosis shown by histopathologic findings in patients with chronic HCV and chronic HBV infections, chronic HBV-infected tissue might have less collagen and more variable inflammatory changes than tissue with chronic HCV infection.…”
Section: Patientsmentioning
confidence: 99%